Characterization of Pancreatic Cancer Tissue Using Multiphoton Excitation Fluorescence and Polarization-Sensitive Harmonic Generation Microscopy - Tokarz, Danielle; Cisek, Richard; Joseph, Ariana; Golaraei, Ahmad; Mirsanaye, Kamdin; Krouglov, Serguei; Asa, Sylvia L.; Wilson, Brian C.; Barzda, Virginijus (Frontiers in Oncology, 2019)
Thin tissue sections of normal and tumorous pancreatic tissues stained with hematoxylin and eosin Y were investigated using multiphoton excitation fluorescence (MPF), second harmonic generation (SHG) and third harmonic generation (THG) microscopies. The cytoplasm, connective tissue, collagen and extracellular structures are visualized with MPF due to the eosin stain, whereas collagen is imaged with endogenous SHG contrast that does not require staining. Cellular structures, including membranous interfaces and nuclear components, are seen with THG due to the aggregation of hematoxylin dye. Changes in the collagen ultrastructure in pancreatic cancer were investigated by a polarization-sensitive SHG microscopy technique, polarization-in, polarization-out (PIPO) SHG. This involves measuring the orientation of the linear polarization of the SHG signal as a function of the linear polarization orientation of the incident laser radiation. From the PIPO SHG data, the second-order nonlinear optical susceptibility ratio, χ(2)zzz’/χ(2)zxx’, was obtained that serves as a structural parameter for characterizing the tissue. Furthermore, by assuming C6 symmetry, an additional second-order nonlinear optical susceptibility ratio, χ(2)xyz’/χ(2)zxx’, was obtained, which is a measure of the chirality of the collagen fibers. Statistically-significant differences in the χ(2)zzz’/χ(2)zxx’ values were found between tumor and normal pancreatic tissues in periductal, lobular and parenchymal regions, whereas statistically-significant differences in the full-width at half maximum (FWHM) of χ(2)xyz’/χ(2)zxx’ occurrence histograms were found between tumor and normal pancreatic tissues in periductal and parenchymal regions. Additionally, the PIPO SHG data were used to determine the degree of linear polarization (DOLP) of the SHG signal, which indicates the relative amount of signal linear depolarization. Statistically significant differences in DOLP values were found between tumor and normal pancreatic tissues in periductal and parenchymal regions. Hence, the differences observed in the χ(2)zzz’/χ(2)zxx’ values, the FWHM of χ(2)xyz’/χ(2)zxx’ values and the DOLP values could potentially be used to aid pathologists in diagnosing pancreatic cancer.